Narrowband-seeded PPLN non-resonant optical parametric oscillator - Temel,T; Murray,RT; Wang,L; Chen,W; Schirrmacher,A; Battle,RA; Petrov,V (Optical Materials Express, 2024)
A PPLN non-resonant optical parametric oscillator injection-seeded by narrowband sub-100-mW CW radiation at the signal wavelength produces > 3 W idler average power at 2376nm for a 20-kHz repetition rate, with a sub-2-nm spectral linewidth. The maximum quantum efficiency reaches 39.5%, roughly 1.4 times higher compared to narrowband operation achieved with a volume Bragg grating at the same pump level. Seed levels as low as 40mW are sufficient to produce the desired spectral narrowing effect.